PENGARUH PEMBERIAN MP-ASI METODE BABY-LED WEANING TERHADAP PERKEMBANGAN PADA BALITA - KAJIAN PUSTALA - Wati, Putu Erna Sintya; Dewi, Anak Ayu Nyoman Trisna Narta; Kamayoga, I Dewa Gede Alit; Nugraha, Made Hendra Satria (Kinetic and Physiotherapy Comprehensive, 2024)
Background: The baby-led weaning (BLW) approach can introduce complementary food to six-month-old infants. This method offers large pieces of solid foods such as vegetables, meat, and fruit. BLW can encourage children's development, especially motor skills such as chewing and speaking. This literature review aimed to determine the definition and technique of the BLW in giving complementary feeding and identify the effect of using the BLW method on toddler development. Methods: The type of research was a literature review based on the review process of research articles that discuss the effect of BLW on toddler development. The search for articles was done from the Google Scholar and PubMed databases. Results: The author found infants were introduced to complementary feeding late from standard weaning. Initially, the baby is offered finger food and allowed to eat alone. BLW significantly affects children's development, especially in helping to form independence, preventing picky eater behaviour, stimulating children's fine motor skills, and improving oral motor skills. Conclusion: The mother offered late complementary feeding with different types of food and techniques from the standard method. The BLW could significantly influence toddler development.